Optimizing the Quality of Tourism Management Services in Sumatra: Integration of Total Quality Management, CRM, and Innovation as Key Factors - Sitorus, Sunday Ade (Formosa Journal of Science and Technology, 2024)
The study aims to analyze the impact of Total Quality Management (TQM), Customer Relationship Management (CRM), and Innovation as factors influencing service quality in service management in Sumatra. The research uses a descriptive quantitative method with a Structural Equation Model and PLS 3.0 application. The sample size is 2433 service providers across Sumatra, and 343 service providers in the study were selected using systematic random sampling. The results show that total quality management, customer relationship management, and Innovation have a significant positive impact on service quality in service management in Sumatra. These factors can be integrated to improve service quality if integrated. The study contributes to the literature on factors influencing service quality in service management. However, the study has limitations, such as a large sample size and focus on service management in Sumatra. The research recommends conducting the study with a larger sample size and using a geographical approach to provide a more comprehensive analysis.